1991
DOI: 10.1152/jn.1991.66.5.1564
|View full text |Cite
|
Sign up to set email alerts
|

Discharge patterns of trigeminal commissural last-order interneurons during fictive mastication in the rabbit

Abstract: 1. The aim of these experiments was to examine the physiological properties and patterns of firing of trigeminal interneurons during fictive mastication in anesthetized and paralyzed rabbits. Antidromic stimulation was used to show that the 82 interneurons projected to the area of the contralateral fifth nerve motor nucleus (NVmot). 2. Straight-line conduction velocities calculated from stereotaxic coordinates of the stimulating and recording electrodes for 63 interneurons were found to range between 3.7 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 0 publications
2
45
1
Order By: Relevance
“…Our data are concordant with the conclusions of most physiological studies, which showed that the latencies of vestibular-elicited masseter muscle responses are too long for these responses to be mediated through direct connections between the VN and Mo5 (Tolu and Pugliatti 1993;Tolu et al 1994Tolu et al , 1996Deriu et al 1999). Potential relays from the VN and PH to masseter motoneurons could include several regions of the pontomedullary reticular formation, particularly the reticular zone surrounding the Mo5, which has been reported to contain neurons that are components of the network responsible for the generation of rhythmic jaw movements (Donga and Lund 1991;Inoue et al 1992;Westberg et al 1998) and to be involved in modulating trigeminal motoneuron activity induced by peripheral and cortical inputs (Sessle 1977;Nozaki et al 1986 a,b;Westberg and Olsson 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Our data are concordant with the conclusions of most physiological studies, which showed that the latencies of vestibular-elicited masseter muscle responses are too long for these responses to be mediated through direct connections between the VN and Mo5 (Tolu and Pugliatti 1993;Tolu et al 1994Tolu et al , 1996Deriu et al 1999). Potential relays from the VN and PH to masseter motoneurons could include several regions of the pontomedullary reticular formation, particularly the reticular zone surrounding the Mo5, which has been reported to contain neurons that are components of the network responsible for the generation of rhythmic jaw movements (Donga and Lund 1991;Inoue et al 1992;Westberg et al 1998) and to be involved in modulating trigeminal motoneuron activity induced by peripheral and cortical inputs (Sessle 1977;Nozaki et al 1986 a,b;Westberg and Olsson 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical procedures were similar to those already published (L und et al, 1984;Olsson et al, 1986b;Donga and L und, 1991). Briefly, a pair of needle electrodes were inserted into the right inferior alveolar nerve (Alv inf).…”
Section: Methodsmentioning
confidence: 99%
“…Such input has also been shown to come from both sides of the head and the upper neck (Sessle et al, 1986;Dallel et al, 1990). The fact that unilateral pain has bilateral jaw motor effects can be due to the projections of trigeminal interneurons to both ipsilateral and contralateral trigeminal motor nuclei (Moore and Appenteng, 1990;Donga and Lund, 1991).…”
Section: Pain and Eccentric Muscle Workmentioning
confidence: 99%